Fictionalised Biography as a New Voice for Women’s Lives in Virginia Woolf’s Orlando and Flush - Maryam Thirriard (Presses Universitaires de la Méditerranée, 2021)
Virginia Woolf reflects on the vulnerability of women’s voices in her essay Three Guineas (1938). More specifically, in Three Guineas, Woolf uses the term ‘influence’, which, according to her, women lack because they have neither financial power nor education, rendering them inaudible. She argues that women remain ‘outsider[s]’ with ‘no right to speak’ (Woolf 2015, 116). By the end of the essay, the reader realises that Woolf has transformed this condition into a form of resistance by refusing to occupy a position in the male-dominated public sphere. In the 1920s, Woolf’s awareness of the inaudibility of women’s lives made her want to write a woman’s life herself, leading to Orlando and then to Flush. Both these fantasised biographies portray women: Orlando (1928) is a fantastical biography of her close friend Vita Sackville-West, and Flush (1933) tells the story of Elizabeth Barret Browning’s life through the biography of her dog. In contrast, Roger Fry is nonfictional. Why did Woolf choose to fictionalise her ‘woman’ biographies? This paper argues that, similarly to Woolf’s unconventional choice in Three Guineas to remain an ‘outsider’ to better fight gender inequality and militarism, fiction can be considered a political tool in that it allows for an alternative mode of biographical representation. Not only does Woolf’s use of fiction enable her to compensate for the lack of visibility of her feminine subjects, but she also develops a writing strategy capable of delivering an innovative, politicized representation of the women she depicted.